Kinetics of Cardiac Remodeling and Fibrosis Biomarkers During an Extreme Mountain Ultramarathon - Le Goff, Caroline; Viallon, Magalie; Kaux, Jean-François; Andonian, Pierre; Moulin, Kevin; Seidel, Laurence; Giardini, Guido; Gergelé, Laurent; Croisille, Pierre; Cavalier, Etienne; Millet, Gregoire P. (Frontiers in Cardiovascular Medicine, 2022)
Objectives The effects of ultra-distance on cardiac remodeling and fibrosis are unclear. Moreover, there are no data reporting the kinetics of cardiac alterations throughout the event and during recovery. Our aim was to investigate the kinetics of biological markers including new cardiac fibrosis biomarkers suppression of tumorigenicity 2 (ST2) and galectin-3 (Gal-3) during and after an extreme mountain ultramarathon. Methods Fifty experienced runners participating in one of the most challenging mountain ultramarathons (330 km, D+ 25,000 m) were enrolled in our study. Blood samples were collected at four time points: before (Pre-), at 148 km (Mid-), at the finish line (Post-), and 3 days after the recovery period (Recov-). Results The cardiac fibrosis biomarkers (ST2 and Gal-3) increased from Pre- to Mid-. During the second half, ST2 remained higher than pre-values as opposed to Gal-3. Necrosis, ischemia, and myocyte injury biomarkers increased until Mid- then decreased but remained higher at Recov- than Pre-values. Oxidative stress appeared at Mid-. Lipid peroxides remained higher at Recov- compared to Pre-. The maximal value in most of these biomarkers was observed at Mid- and not at Post-. Conclusions The present study supports biphasic kinetics of cardiac fibrosis biomarkers, with a relative recovery during the second half of the event that seems specific to this extreme event. Overall, performing at such an extreme ultramarathon seems less deleterious for the heart than shorter events.